2012
DOI: 10.1589/jpts.24.557
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Burden of Family Caregivers of the Home-bound Elderly Disabled

Abstract: Abstract.[Purpose] The purpose of this study was to clarify the factors affecting the burden of family caregivers of home-bound disabled elderly persons.[Subjects] Data were collected for 66 home-bound disabled elderly persons (mean age of 81.4 ± 9.7) and their 66 family caregivers (mean age of 62.4 ± 11. 5) who were living at home in Kobe city, Hyogo.[Method] Capacity to perform ADL was assessed using the Barthel Index for the home-bound disabled elderly persons. The care burden and health status of their fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 9 publications
1
11
0
2
Order By: Relevance
“…Onishi et al (2005), for their part, stated that higher morale is significantly correlated with independence in ADL. Further, it was identified that people who were functionally independent have higher morale (von HeidekenWagert et al, 2005;Takemasa, 1998;Sanchez del Corral et al, 1996). Hence, we hypothesize the following: H5: Better functional ability leads to a higher elderly morale.…”
Section: Functional Abilitymentioning
confidence: 87%
See 2 more Smart Citations
“…Onishi et al (2005), for their part, stated that higher morale is significantly correlated with independence in ADL. Further, it was identified that people who were functionally independent have higher morale (von HeidekenWagert et al, 2005;Takemasa, 1998;Sanchez del Corral et al, 1996). Hence, we hypothesize the following: H5: Better functional ability leads to a higher elderly morale.…”
Section: Functional Abilitymentioning
confidence: 87%
“…Previous studies have found that there exists an association between functional ability and morale (Onishi, Matuda, Suzuki, Endo, & Iguchi, 2005;Kudo et al, 2007;von HeidekenWagert et al, 2005;Takemasa, 1998;Sanchez del Corral et al, 1996). In a study conducted by Kudo et al (2007) on the relationship between morale and family composition in both self-care dependent and independent older people, results showed that self-care independent people have higher morale when they live together with their family.…”
Section: Functional Abilitymentioning
confidence: 95%
See 1 more Smart Citation
“…The PGCMS is now widely used as a measure of morale, psychological well-being, and QOL in elderly populations in both the community [1,[4][5][6][7][8][9] and institutions [2,8,10].…”
Section: Instrumentsmentioning
confidence: 99%
“…Living in ordinary housing with family members, family support [6], social activities [44] and not feeling lonely [7,44] are the social factors that are most strongly associated with PGCMS scores. In the present study, the association between social support and morale was not surprising, because lonely dissatisfaction is a subscale of the PGCMS.…”
Section: Convergent-divergent Validitymentioning
confidence: 99%